Gynecological complications in long-term survivors after allogeneic hematopoietic cell transplantation—a single-center real-life cross-sectional study - Su, Huina; Zhou, Xinyu; Zhao, Yanli; Lu, Yue; Liu, DeYan; Zhang, Janping; Yang, Xin (Frontiers in Medicine, 2022)
Background and objectives Hematopoietic stem cell transplantation (HCT) is a treatment for hematopoietic diseases. However, most cured female patients may suffer from premature ovarian insufficiency (POI) after HCT, which is mainly caused by the pre-HCT conditioning regimen. Hence this study aims to explore the impact of HCT treatment on reproductive and ovarian functions in female survivors. Methods 55 female participants under the age of 40, who underwent HCT and met the inclusion criteria were enrolled. Data related to blood disease, menstruation and fertility in the 3 years following HCT were collected. Results The involved patients received transplantation at different age stages, ranging from 8 to 37. All patients, except those with aplastic anemia (AA; 5/55), received a myeloablative conditioning regimen, usually modified total body irradiation/cyclophosphamide (TBI/Cy; 25/55) or modified Busulfan/cyclophosphamide (Bu/Cy; 23/55). Among women (42/55) who menstruated before HCT, 16.67%(7/42) had a spontaneous menstrual relapse and 83.3%(35/42) had amenorrhea after HCT. 72.7%(40/55) could be regarded as having POI. This proportion included 100%(25/25) of women aged 21-40 at the time of HCT, 62.5% (15/24) of those aged 11-20, and 0% (0/6) of those ≤10 years old. Patients with AML were more likely to have POI (95.7%). Patients aged ≤10 years (0%) or 11-20 years (16.7%) at the time of HCT were less likely to have moderate to severe menopause than those 21-40 years old (44.0%). Conclusion The prevalence of POI following HCT was high and POI was associated with age, conditioning regimen, and type of blood disease.